Generasi z dan pancasila: membangun dialog yang konstruktif di ruang publik digital - Matondang, Muthia Hafidzah Syahzanan (Maliki Interdisciplinary Journal, 2025)
As the foundation and ideology of the Indonesian nation, Pancasila functions as a legal symbol as well as a representation of humanity. Generation Z, who grew up and live in the era of digital technology, has a very strategic approach in improving Pancasila through digital public spaces. As a generation that is active on social media, Generation Z has great potential in creating constructive dialogue that fosters social cohesion and national values. The aim of this research is to understand how Generation Z can create constructive dialogue in digital public spaces. It is hoped that this can be a reference in helping develop generation Z who think critically, have a strong sense of self-esteem, and have a strong commitment to healthy and productive digital communication.